A Review of Common Problems in Linguistic Resources and a New Way to Represent Ontological Relations - Vaquero, Antonio (2007)
Existing lexical resources have taxonomic structure related problems that negatively impact the results of domain-specific applications. This is the result of an approach that focuses on implementation and content issues rather than on questions of design, semantic cleanness and application usefulness. Although taxonomy structuring methodologies have been developed to correct some of these problems, they remain too general and far from the problem-solving and domain-specific approach that ontology-based linguistic resources need in order to be problem-solving. Based on a short analysis of some common problems in lexical resources and of the available taxonomy structuring methodologies, we propose the use of a set of ideas that may be useful in the design and development of an application-oriented ontology-based linguistic resource, and help developers in refining the meaning of concepts and relations to avoid the common problems present in linguistic resources. In addition, we present an E-R model where these ideas have been integrated to better illustrate our proposal and enhance our methodology for the construction of ontology-based linguistic resources.